1985
DOI: 10.1111/j.1600-051x.1985.tb01378.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of self‐administered daily irrigation with 0.02% SnF2 on periodontal disease activity

Abstract: To determine the effect on periodontal health of a daily self-administered irrigation with 0.02% stannous fluoride (SnF2) solution, 28 subjects who had moderate to advanced periodontitis were randomly divided into 3 groups: a control group (n = 9) which used no irrigation, a group (n = 8) which used a self-administered water irrigation device (Water Pik) daily with water (H2O group) and a group (n = 11) which used the Water Pik in a similar manner but with SnF2 solution (SnF2 group). All subjects were instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…The other treatment group, which used a 0.4% SnF2 gel with less than 2% available Sn2+ ions, showed no significant differences from the control group, whether the gel was used once or twice daily during the nine-month study period. This study is in agreement with previous clinical trials that have found SnF2 to have beneficial effects on periodontal status (Boyd et al, 1985;Saxton et al, 1986).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The other treatment group, which used a 0.4% SnF2 gel with less than 2% available Sn2+ ions, showed no significant differences from the control group, whether the gel was used once or twice daily during the nine-month study period. This study is in agreement with previous clinical trials that have found SnF2 to have beneficial effects on periodontal status (Boyd et al, 1985;Saxton et al, 1986).…”
Section: Discussionsupporting
confidence: 93%
“…These effects appear to be related to the availability of the Sn2+ ion rather than the F-ion (Camosci and Tinanoff, 1984). Other clinical reports have demonstrated that topically applied SnF2 is associated with reduction of supragingival plaque, motile subgingival plaque micro-organisms, gingivitis, and pocket depth (for review, see Boyd et al, 1985). SnF2 has been topically applied in various vehicles, such as mouthrinses, glycerine-base gels, and irrigating solutions.…”
Section: Introductionmentioning
confidence: 97%
“…Derkson & 0.4% SnF: to their abutment teeth. Boyd et al (1985) found an approxi-MacEntee (1982) reported a 20% re-mate 65% reduction in subjects classiduction in gingival index in those sub-fied as having moderate to severe perio-dontitis, who irrigated their pockets daily with 0,02% SnF:. Frankel et al (1985) showed a 30% reduction in GI scores in subjects who rinsed with 0.1% SnF2 after periodontal surgery, Boyd et al, (1988) also found a 60% reduction in GI scores in orthodontic subjects brushing twice daily with Q.A'Vo SnF2.…”
Section: Discussionmentioning
confidence: 99%
“…Significant reductions in gingivitis, due to topical applications of SnF?. have been found in several studies (Mazza et al 1981, Derkson & MacEntee 1982. Boyd et al 1985, Frankel et al 1985, Boyd et al 1988), yet others have reported marginal or no effect (Leverett et al 1984, Wolff et al 1988).…”
mentioning
confidence: 94%
“…In recent years administrations of 0.01-1.64% SnF2 have resulted in a significant reduction of human periodontal disease (3,17). The precise contribution of the Sn++ and F" ions in the antibacterial action of SnFa has not been delineated.…”
Section: Introductionmentioning
confidence: 99%